Electrolyte-resistant and high-temperature-resistant lithium battery termination adhesive tape
By using hybrid polyurethane and perfluoropolyamide materials in lithium battery termination tape, a stable chemical bond and spatial mesh structure is formed, which solves the problem of insufficient resistance of lithium battery termination tape in high temperature and electrolyte, and improves its high temperature resistance , electrolyte resistance and mechanical properties ensure the safety and stability of lithium batteries.
Patent Information
- Application Number
- CN202411561403.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium battery termination tape has insufficient resistance in high temperatures and electrolytes, resulting in unstable performance and low safety of lithium batteries.
Using pressure-sensitive adhesive layer and substrate layer including hybrid polyurethane and perfluoropolyamide, the materials introduced by modifying silane and fluorine groups are formed to form a stable chemical bond structure and a complex spatial network structure to enhance the mechanical strength and resistance of the material. Electrolyte properties.
It significantly improves the high temperature resistance, electrolyte and mechanical properties of lithium battery termination tape, ensuring the safety and stability of lithium battery in the case of leakage and combustion.
Smart Images

Figure CN119242206A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tape processing, in particular to an electrolyte-resistant and high-temperature-resistant lithium battery termination tape. Background Art
[0002] Lithium battery termination tape technology has undergone rapid development from basic material optimization to the application of multifunctional composite materials. The traditional polymer materials used in the early days could not meet the needs of high-energy density batteries, especially in the environment of electrolyte corrosion and high temperature. With the deepening of research, scientists have improved the electrolyte resistance and high temperature resistance of the tape through polymer modification and introduction of composite materials. These advances have greatly improved the safety and life of lithium batteries and promoted the further development of battery technology.
[0003] Prior art CN115353819B discloses a rubber-type pressure-sensitive adhesive tape for lithium batteries, comprising the following raw material components by weight: 60-90 parts of natural rubber, 35-50 parts of styrene-butadiene rubber, 20-30 parts of methyl methacrylate, 10-15 parts of vinyl acetate, 0.1-2 parts of azobisisobutylene, 0.1-1 parts of isocyanate, 1-3 parts of antioxidant, 5-10 parts of zinc oxide, 3-8 parts of white carbon black and 300-500 parts of toluene. The release layer of the pressure-sensitive adhesive tape has good surface properties, demoulding properties and barrier properties. The adhesive layer uses a blend of natural rubber and styrene-butadiene rubber as the main material, and after cross-linking and modification with polar monomers, the initial adhesion and peel strength of the pressure-sensitive adhesive are improved. At the same time, the rubber-type pressure-sensitive adhesive is less affected by the lithium battery electrolyte and still maintains excellent performance in the electrolyte.
[0004] The pressure-sensitive adhesive is obtained by melt-mixing natural rubber with various auxiliary materials and then coating the mixture on a substrate to obtain a pressure-sensitive adhesive tape for lithium batteries. However, the polarity difference between the organic component and the inorganic component in the material is large, which makes the interface bonding force between the materials weak, resulting in uneven parts of the adhesive layer during the coating and drying process, resulting in differences in the adhesion properties of different pressure-sensitive adhesives. The instability of the internal structure causes the pressure-sensitive adhesive to be unstable in a high-temperature working environment, and is corroded by the electrolyte during the battery discharge process, resulting in unstable electrolyte properties, thereby affecting the performance of the lithium battery.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide an electrolyte-resistant and high-temperature-resistant lithium battery termination tape, so as to solve the technical problem in the prior art that the electrolyte-resistant and high-temperature-resistant performance of lithium battery termination tapes needs to be further improved.
[0007] The object of the present invention can be achieved by the following technical scheme: an electrolyte-resistant and high-temperature-resistant lithium battery termination tape comprises a pressure-sensitive adhesive layer and a base layer;
[0008] The pressure-sensitive adhesive layer comprises the following raw materials by weight: 60-80 parts of hybrid polyurethane, 10-30 parts of tackifier, 10-15 parts of thermosetting agent, 5-10 parts of plasticizer, 10-15 parts of solvent and 0.5-2 parts of antioxidant;
[0009] The base layer comprises the following raw materials in weight: 50-60 parts of perfluoropolyamide, 10-15 parts of anti-adhesive agent, 10-20 parts of solvent, 5-8 parts of thermal curing agent, 5-10 parts of plasticizer and 0.5-2 parts of antioxidant.
[0010] Furthermore, the tackifier is one or more of rosin glycerol ester, petroleum resin and terpene resin; the anti-adhesive agent is one or more of polytetrafluoroethylene, paraffin and silicone oil; the solvent is one or more of toluene, acetone and ethyl acetate; the thermosetting agent is one or more of hexamethylenetetramine, trimethylolpropane triacrylate and melamine formaldehyde resin; the plasticizer is one or more of dibutyl phthalate, dioctyl phthalate and epoxy soybean oil; the antioxidant is one or more of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and triphenyl phosphite.
[0011] Furthermore, the preparation method of the hybrid polyurethane comprises the following steps:
[0012] A1. Add allyltrimethoxysilane and dichloromethane to a low-temperature reaction kettle and stir. After the low-temperature reaction temperature is reduced to -80°C, ozone is introduced into the reaction kettle at a rate of 0.2-0.5L / min. The reaction is kept warm for 10-15min. After the reaction is completed, the reaction solution is collected after the temperature of the reaction kettle is raised to room temperature to obtain an oxidizing solution.
[0013] A2, adding the oxidizing liquid and dimethyl sulfide into the reactor, stirring at room temperature for 20-30 minutes, and post-treating to obtain modified silane;
[0014] The reaction equation for preparing modified silane is:
[0015]
[0016] The reaction principle for preparing modified silanes is as follows: at low temperatures, ozone reacts with the carbon-carbon double bond of olefins through an electrophilic addition reaction to form an ozonide intermediate. The ozone molecule first forms a three-membered ring peroxide with the double bond of the olefin. This unstable intermediate is rapidly converted into a more stable ozonide. Dimethyl sulfide acts as a reducing agent in this step, reacting with the ozonide to reduce the oxidizing part, breaking the ozonide ring, and generating two carbonyl compounds. For allyltrimethoxysilane, the carbon atoms at both ends of the carbon-carbon double bond will be oxidized to aldehyde groups, thereby generating a modified silane with an aldehyde group.
[0017] A3. Add chain-extended polyurethane, modified silane, 3-trifluoromethylpropiophenone, γ-alumina and dimethyl sulfoxide into a reactor, increase the temperature of the reactor to 60-80°C, keep the reaction temperature for 2-3 hours, and obtain hybrid polyurethane after post-treatment.
[0018] The reaction equation for preparing hybrid polyurethane is:
[0019]
[0020] Where:
[0021] The reaction principle for preparing hybrid polyurethanes is as follows: under acidic conditions, the carbonyl oxygen of the aldehyde is protonated, which significantly increases the electrophilicity of the carbonyl carbon, and undergoes a nucleophilic addition reaction with the secondary amine to form an imine intermediate. The reactants continue to undergo a deprotonation reaction of the α-hydrogen to generate an enol intermediate, which acts as a nucleophilic reagent to attack the previously generated imine intermediate to form a new CC bond, thereby ultimately preparing a hybrid polyurethane.
[0022] Furthermore, in step A1, the amount ratio of allyltrimethoxysilane and dichloromethane is 3-5g:15-20mL; in step A2, the stirring rate is 80-120rpm, the amount ratio of the oxidizing liquid and dimethyl sulfide is 10-15mL:3-5g, and the post-treatment includes: after the reaction is completed, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain modified silane; in step A3, the amount ratio of the extended polyurethane, modified silane, 3-trifluoromethylpropiophenone, γ-alumina and dimethyl sulfoxide is 15-20g:2-5g:4-6g:0.5-0.8g:60-80mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a hybrid polyurethane.
[0023] Further, the preparation method of the chain-extended polyurethane is:
[0024] B1. Add 1,3,5-triacyl cyanurate, dichloromethane and tetrabutylammonium bromide into a reactor and stir. After the temperature of the reactor is raised to 30-50° C., add the epoxidation liquid into the reactor, keep the temperature for 1-2 hours, and perform post-treatment to obtain an epoxidation chain extender.
[0025] The reaction equation for preparing the epoxidation chain extender is:
[0026]
[0027] The reaction principle for preparing the epoxidation chain extender is as follows: tetrabutylammonium bromide acts as a phase transfer catalyst in the reaction, and it transfers hydrogen peroxide in the aqueous phase to the organic phase. The cation part of tetrabutylammonium bromide combines with the hydrogen peroxide anion to form a lipophilic ion pair BuN+HOO-, which dissolves in the organic phase, allowing hydrogen peroxide to enter the organic phase. When hydrogen peroxide enters the organic phase, the oxygen in hydrogen peroxide is activated by the double bond, attacks the allyl double bond in 1,3,5-triallyl cyanurate, and undergoes cycloaddition to generate a ternary epoxy structure; triethylamine acts as an alkaline auxiliary agent, which plays a role in stabilizing the system in the reaction. During the epoxidation process, hydrogen peroxide partially decomposes to generate water, and triethylamine can neutralize this part of water, maintain a suitable alkaline environment, promote the epoxidation reaction, and prevent the reaction from stopping or reversing.
[0028] B2, adding the epoxidation chain extender, diethyl phosphite, triethylamine and N,N-dimethylformamide into the reactor, raising the temperature of the reactor to 60-80°C, keeping the temperature for reaction for 1-3h, and post-treating to obtain the modified chain extender;
[0029] The reaction equation for preparing the modified chain extender is:
[0030]
[0031] Where:
[0032] The reaction principle for preparing the modified chain extender is as follows: the phosphorus-hydrogen bond in diethyl phosphite is nucleophilic. In the presence of triethylamine, the nucleophilicity of the PH bond is enhanced. The phosphorus atom, as a nucleophilic center, attacks a carbon atom of the epoxy group, causing the epoxy three-membered ring to open, and finally the modified chain extender is prepared.
[0033] B3. Add the modified chain extender, triethylamine and dimethyl sulfoxide into the reactor and stir. The temperature of the reactor is raised to 50-60°C. After stirring for 10-15 minutes, the modified polyurethane is added into the reactor. After the reaction is carried out for 40-60 minutes, the chain-extended polyurethane is obtained by post-treatment.
[0034] The reaction equation for preparing chain-extended polyurethane is:
[0035]
[0036] Where:
[0037] The reaction principle for preparing chain-extended polyurethane is as follows: the carbon atom of the isocyanate group in the modified polyurethane is connected to the nitrogen and oxygen with strong electronegativity, making it partially positively charged and making it easy to be attacked by the nucleophilic hydroxyl group in the modified chain extender. Through continuous polymerization and regulation of the amount of modified chain extender, a chain-extended polyurethane terminated with isocyanate group is finally prepared.
[0038] Further, in step B1, the amount ratio of 1,3,5-triacyl cyanurate, dichloromethane and tetrabutylammonium bromide to the epoxidation liquid is 5-8g:20-30mL:1.2-1.6g:20-25mL, and the epoxidation liquid is prepared by 20-30wt% aqueous hydrogen peroxide solution and triethylamine in an amount ratio of 8-10mL:1g, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is carried out until no liquid is extracted to obtain an epoxidation chain extender; in step B2, the amount ratio of the epoxidation chain extender, diethyl phosphite, triethylamine and N,N-dimethylformamide is 8-10 g:2-3g:0.3-0.5g:50-60mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain a modified chain extender; in step B3, the stirring rate of the reactor is 120-180rpm, and the amount ratio of the modified chain extender, triethylamine, dimethyl sulfoxide and modified polyurethane is 3-5g:0.5-0.8g:60-80mL:15-20g, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain a chain extended polyurethane.
[0039] Furthermore, the preparation method of the modified polyurethane is as follows: 2,3,5,6-tetrafluorophenylenedimethanol, triethylamine and dimethyl sulfoxide are added to a reactor and stirred, the temperature of the reactor is increased to 50-60°C, and after stirring for 10-15 minutes, 1,3-diisocyanatotoluene is added to the reactor, and after the reaction is carried out for 40-60 minutes, the modified polyurethane is obtained by post-treatment.
[0040] The reaction equation for preparing modified polyurethane is:
[0041]
[0042] The reaction principle for preparing modified polyurethane is as follows: the carbon atom of the isocyanate group in 1,3-diisocyanatotoluene is connected to the nitrogen and oxygen with strong electronegativity, making it partially positively charged and making it easy to be attacked by the nucleophilic reagent hydroxyl group in 2,3,5,6-tetrafluorophenylenediol. Through continuous polymerization and regulation of the amount of reactive monomers, an extended chain polyurethane terminated with isocyanate groups is finally prepared.
[0043] Furthermore, the stirring rate of the reactor is 120-180 rpm, the amount ratio of 2,3,5,6-tetrafluorophenylenediol, triethylamine, dimethyl sulfoxide and 1,3-diisocyanatotoluene is 5-8 g:0.5-0.8 g:60-80 mL:8-12 g, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100° C., and the reduced pressure distillation is performed until no liquid is extracted to obtain a modified polyurethane.
[0044] Furthermore, the preparation method of perfluoropolyamide comprises the following steps:
[0045] C1, adding 5,5'-methylenedisalicylic acid, 2,4-diamino-6-[4-(trifluoromethyl)phenyl]-1,3,5-triazine, triethylamine and dimethyl sulfoxide into a reaction kettle, raising the temperature of the reaction kettle to 60-80°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain modified polyamide;
[0046] The reaction equation for preparing modified polyamide is:
[0047]
[0048] Where:
[0049] The reaction principle for preparing modified polyamide is as follows: 5,5'-methylenedisalicylic acid and 2,4-diamino-6-[4-(trifluoromethyl)phenyl]-1,3,5-triazine undergo polymerization reaction under alkaline conditions, and by controlling the amount of the reaction monomers, a modified polyamide terminated with amino groups is finally formed.
[0050] C2. Add modified polyamide, perfluorooctane sulfonyl fluoride, triethylamine and dimethyl sulfoxide into a reactor and stir. Lower the temperature of the reactor to 0-5°C, keep warm and stir for 1-2 hours, and perform post-treatment to obtain perfluoropolyamide.
[0051] The reaction equation for preparing perfluoropolyamide is:
[0052]
[0053] Where:
[0054] The reaction equation for preparing perfluoropolyamide is: under the catalysis of alkaline conditions, the acyl fluoride bond on perfluorooctanesulfonyl fluoride reacts with the amino group on the modified polyurethane, a large number of fluorine groups are introduced into the modified polyurethane, and finally perfluoropolyamide is prepared.
[0055] Furthermore, in step C1, the amount ratio of 5,5'-methylenedisalicylic acid, 2,4-diamino-6-[4-(trifluoromethyl)phenyl]-1,3,5-triazine, triethylamine and dimethyl sulfoxide is 5-8g:3-5g:0.3-0.5g:40-60mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a modified polyamide; in step C2, the amount ratio of modified polyamide, perfluorooctane sulfonyl fluoride, triethylamine and dimethyl sulfoxide is 10-15g:3-5g:0.3-0.5g:60-80mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a perfluoropolyamide.
[0056] Further, the preparation method of the termination tape comprises the following steps:
[0057] S1. The perfluoropolyamide, anti-adhesive agent, solvent, thermosetting agent, plasticizer and antioxidant are uniformly mixed, and then melt-extruded, preheated, stretched, heat-set and rolled to obtain a rolled base layer with a thickness of 20-30 μm and a width of 5-20 mm;
[0058] S2. The hybrid polyurethane, tackifier, solvent, thermosetting agent, plasticizer and antioxidant are mixed evenly and then melt-extruded and coated on the upper surface of the base layer to obtain a pressure-sensitive adhesive layer with a thickness of 20-30 μm, and then post-processed to obtain a termination tape.
[0059] Furthermore, the specific operation steps in step S1 are: after mixing the materials evenly, put them into a twin-screw extruder to melt and extrude them into a mold; after the materials are cooled, place the materials in a stretching machine, set the temperature of the stretching machine to 100-120°C, control the longitudinal stretching ratio to 4-6:1, and the transverse stretching ratio to 8-12:1; after stretching, transfer the film to a cooling system, set the temperature of the cooling system to 20-40°C, cool and form for 1-2 hours, and obtain a stretched film; after cutting by a CNC machine tool, obtain a strip base layer with a thickness of 20-30μm and a width of 5-20mm; and after winding by a winder, obtain a rolled base layer.
[0060] Furthermore, in step S2, post-processing includes: placing the coated base layer into a drying oven at a temperature of 10-15°C for cold air drying, the cold air temperature is 10-15°C, the wind speed is 8-10m / s, and drying until the coating temperature drops to room temperature. After drying, use a winder to wind it up, and the winding stress is controlled at 30-50N / m to obtain a termination tape.
[0061] The reaction principle for preparing the termination tape is as follows: at high temperature, the isocyanate groups in the hybrid polyurethane react with the hydroxyl groups in the perfluoropolyamide, so that the base layer and the pressure-sensitive adhesive layer are tightly bonded, and finally the termination tape is prepared.
[0062] The present invention has the following beneficial effects:
[0063] 1. In the lithium battery termination tape prepared by the present invention, during the high-temperature coating process of the base layer and the pressure-sensitive adhesive layer, the residual hydroxyl groups on the surface of the base layer react with the residual isocyanate groups on the surface of the pressure-sensitive adhesive layer at high temperature to form a stable structure linked by chemical bonds, thereby improving the overall mechanical strength of the pressure-sensitive adhesive; in the process of preparing each hierarchical structure, a large number of fluorine groups are introduced into the organic components, and the electrolyte resistance and high temperature resistance of the termination tape are significantly improved through the coordination of the base layer and the pressure-sensitive adhesive layer; if the lithium battery leaks and burns, the modified cross-linking agent chain segments in the hybrid polyurethane component in the pressure-sensitive adhesive layer will decompose to produce acidic substances to promote the carbonization of the pressure-sensitive adhesive layer and the base layer, and during the carbonization process, the silane coupling agent component in the hybrid polyurethane ensures that the carbonized layer adheres to the surface of the battery structure to prevent the further spread of the fire, and the safety of the lithium battery is ensured through the coordinated coordination of the hierarchical structure. Through the modification between materials and the coordinated coordination between hierarchical structures, the present invention finally obtains a flame-retardant termination tape that is resistant to electrolyte, resistant to high temperature, has high mechanical properties, and high viscosity.
[0064] 2. In the process of preparing a lithium battery termination tape, the present invention prepares a hybrid polyurethane as the main component of the pressure-sensitive adhesive layer. In the process of preparing the hybrid polyurethane, firstly, a monomer with a large number of fluorine groups is selected to prepare a modified polyurethane, so that it has certain chemical stability and high temperature resistance, and the triazine ring organic matter is modified, and a modified chain extender is obtained by epoxidation and ring-opening reaction. The modified chain extender is cross-linked to make the modified polyurethane produce a complex spatial network structure to obtain an extended chain polyurethane, so that the mechanical properties of the material are further improved, and the active functional groups on the silane coupling agent are further oxidized to obtain modified silane. The modified silane and the organic matter with a large number of fluorine groups are used to modify the extended chain polyamide. Through the introduction of silane coupling agents and fluorine groups, the bonding force between the material and the inorganic surface, the high temperature resistance and the electrolyte resistance are further improved, and finally a hybrid polyurethane is prepared.
[0065] 3. In the process of preparing the lithium battery termination tape of the present invention, a perfluoropolyamide is prepared as the main component of the base layer. In the process of preparing the perfluoropolyamide, a triazine ring having a benzene ring and a fluorine group and an organic matter having a large number of benzene rings are first selected as monomers, and a modified polyurethane with high mechanical strength, electrolyte resistance and high temperature resistance is synthesized through polymerization reaction, and a large number of fluorine groups are introduced into the organic chain segment after polymerization with perfluorooctane sulfonyl fluoride, so that the electrolyte resistance and high temperature resistance of the material are further improved, and finally perfluoropolyamide is obtained, and there are a large number of hydroxyl groups on its surface. In the process of high-temperature coating of the pressure-sensitive adhesive layer, the residual hydroxyl groups on the surface are further combined with the isocyanate groups in the hybrid polyurethane component in the pressure-sensitive adhesive to form a stable structure linked by chemical bonds, so that the structure of the termination tape is further stabilized, and the mechanical strength and wear resistance of the termination tape are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0067] Figure 1 A schematic diagram of the structure of the termination tape segment prepared by the present invention;
[0068] Figure 2 The SEM image of the hybrid polyurethane prepared in the present invention;
[0069] In the figure: 100, pressure-sensitive adhesive layer; 200, base layer. DETAILED DESCRIPTION
[0070] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0071] Example 1
[0072] This embodiment is used to provide an electrolyte-resistant and high-temperature-resistant lithium battery termination tape and a preparation method thereof, comprising the following steps:
[0073] S1. Preparation of perfluoropolyamide
[0074] Weigh: 10.0 g of 5,5'-methylenedisalicylic acid, 6.0 g of 2,4-diamino-6-[4-(trifluoromethyl)phenyl]-1,3,5-triazine, 0.8 g of triethylamine and 90.0 mL of dimethyl sulfoxide and add them into a reactor. The temperature of the reactor is raised to 60° C. and the reaction is kept warm for 2 hours. After the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid is produced to obtain a modified polyamide.
[0075] Weigh: 24.0 g of modified polyamide, 8.0 g of perfluorooctane sulfonyl fluoride, 0.8 g of triethylamine and 120.0 mL of dimethyl sulfoxide, add into a reactor and stir, lower the temperature of the reactor to 5°C, keep warm and stir for 1 hour, after the reactor is cooled to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain perfluoropolyamide.
[0076] S2. Preparation of chain-extended polyurethane
[0077] Weigh: 12.0 g of 2,3,5,6-tetrafluorophenylenedimethanol, 1.2 g of triethylamine and 120.0 mL of dimethyl sulfoxide, add them to a reactor and stir, raise the temperature of the reactor to 50°C, and stir at a rate of 120 rpm. After stirring for 10 minutes, add 16.0 g of 1,3-diisocyanatotoluene to the reactor, and keep the reaction for 40 minutes. After the reactor is cooled to room temperature, add the reaction solution to a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain a modified polyurethane;
[0078] Weigh: 8.0 mL of 20 wt% hydrogen peroxide aqueous solution and 1.0 g of triethylamine were added into a reaction kettle, stirred at room temperature for 2 min at a stirring rate of 30 rpm to obtain an epoxidation solution;
[0079] Weigh: 12.0g of 1,3,5-triacyl cyanurate, 40.0mL of dichloromethane and 3.0g of tetrabutylammonium bromide are added to a reactor and stirred. After the temperature of the reactor is raised to 30°C, 20.0mL of epoxidation liquid is added to the reactor and the reaction is kept warm for 1h. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and the epoxidation chain extender is obtained by vacuum distillation until no liquid is produced;
[0080] Weigh: 18.0 g of epoxidation chain extender, 5.0 g of diethyl phosphite, 0.8 g of triethylamine and 100.0 mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 60°C, keep the temperature for 1 hour, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain a modified chain extender;
[0081] Weigh: 8.0g of modified chain extender, 1.2g of triethylamine and 120.0mL of dimethyl sulfoxide, add into the reactor and stir, the temperature of the reactor is raised to 50°C, the stirring rate is 120rpm, after keeping warm and stirring for 10min, 32.0g of modified polyurethane is added into the reactor, after keeping warm and reacting for 40min, the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain a chain extended polyurethane.
[0082] S3. Preparation of hybrid polyurethane
[0083] Weigh: 8.0 g of allyltrimethoxysilane and 32.0 mL of dichloromethane are added to a low-temperature reactor and stirred. After the low-temperature reaction temperature is reduced to -80°C, ozone is introduced into the reactor at a rate of 0.2 L / min, and the reaction is kept warm for 10 minutes. After the reaction is completed, the reaction solution is collected after the temperature of the reactor is raised to room temperature to obtain an oxidized solution;
[0084] Weigh: 24.0 mL of oxidation solution and 8.0 g of dimethyl sulfide are added to the reactor, stirred at room temperature for 20 min, and the stirring rate is 80 rpm. After the reaction is completed, the reaction solution is added to a rotary evaporator with a water bath temperature of 80° C., and distilled under reduced pressure until no liquid is produced to obtain modified silane;
[0085] Weigh: 32.0g of extended chain polyurethane, 8.0g of modified silane, 10.0g of 3-trifluoromethylpropiophenone, 1.2g of γ-alumina and 60.0mL of dimethyl sulfoxide and add them into a reactor. The temperature of the reactor is raised to 60°C and the reaction is kept warm for 2h. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain a hybrid polyurethane.
[0086] S4. Preparation of termination tape
[0087] Weigh: 50.0g perfluoropolyamide, 10.0g silicone oil, 10.0g acetone, 5.0g hexamethylenetetramine, 5.0g dibutyl phthalate and 0.5g 2,6-di-tert-butyl-p-cresol, mix the materials evenly and put them into a twin-screw extruder to melt and extrude them into a mold. After the materials are cooled, they are placed in a stretching machine, the temperature of the stretching machine is set to 100°C, the longitudinal stretching ratio is controlled to be 4:1, and the transverse stretching ratio is controlled to be 8:1. After the stretching is completed, the film is transferred to a cooling system, the temperature of the cooling system is set to 20°C, and the film is cooled and formed for 1h to obtain a stretched film. After cutting with a CNC machine tool, a strip-shaped base layer with a thickness of 20μm and a width of 10mm is obtained, and a roll-shaped base layer 200 is obtained after winding with a winder;
[0088] Weigh: 60.0g hybrid polyurethane, 10.0g petroleum resin, 10.0g hexamethylenetetramine, 5.0g dibutyl phthalate, 10.0g acetone and 0.5g 2,6-di-tert-butyl-p-cresol, mix the materials evenly, put them into a twin-screw extruder for melt extrusion coating on the upper surface of the base layer 200 to obtain a pressure-sensitive adhesive layer 100 with a thickness of 20μm, put the coated base layer 200 into a drying oven at a temperature of 10°C for cold air drying, the cold air temperature is 10°C, the wind speed is 8m / s, and it is dried until the coating temperature drops to room temperature. After drying, use a winder to wind it up, and the winding stress is controlled at 30N / m to obtain a termination tape.
[0089] Example 2
[0090] This embodiment is used to provide an electrolyte-resistant and high-temperature-resistant lithium battery termination tape and a preparation method thereof, comprising the following steps:
[0091] S1. Preparation of perfluoropolyamide
[0092] Weigh: 12.0 g of 5,5'-methylenedisalicylic acid, 8.0 g of 2,4-diamino-6-[4-(trifluoromethyl)phenyl]-1,3,5-triazine, 0.8 g of triethylamine and 100.0 mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 60°C, keep the temperature for 2 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain a modified polyamide;
[0093] Weigh: 20.0 g of modified polyamide, 8.0 g of perfluorooctane sulfonyl fluoride, 1.0 g of triethylamine and 120.0 mL of dimethyl sulfoxide, add into a reactor and stir, lower the temperature of the reactor to 5°C, keep warm and stir for 2 hours, after the reactor is cooled to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain perfluoropolyamide.
[0094] S2. Preparation of chain-extended polyurethane
[0095] Weigh: 12.0 g of 2,3,5,6-tetrafluorophenylenedimethanol, 1.2 g of triethylamine and 120.0 mL of dimethyl sulfoxide are added to a reactor and stirred. The temperature of the reactor is raised to 50° C., the stirring rate is 180 rpm, and after heat preservation and stirring for 15 minutes, 20.0 g of 1,3-diisocyanatotoluene is added to the reactor. After heat preservation and reaction for 60 minutes, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100° C., and reduced pressure distillation is performed until no liquid is produced to obtain a modified polyurethane;
[0096] Weigh: 10.0 mL of 20-30 wt% hydrogen peroxide aqueous solution and 1.0 g of triethylamine are added to a reaction kettle, stirred at room temperature for 3 min at a stirring rate of 50 rpm to obtain an epoxidation solution;
[0097] Weigh: 16.0g of 1,3,5-triacyl cyanurate, 50.0mL of dichloromethane and 3.2g of tetrabutylammonium bromide are added to a reactor and stirred. After the temperature of the reactor is raised to 50°C, 25mL of epoxidation liquid is added to the reactor and the reaction is carried out for 2h. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain an epoxidation chain extender;
[0098] Weigh: 18.0g of epoxidation chain extender, 5.0g of diethyl phosphite, 0.8g of triethylamine and 100.0mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 80°C, keep the temperature for 3h, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain a modified chain extender;
[0099] Weigh: 8.0g of modified chain extender, 1.5g of triethylamine and 120.0mL of dimethyl sulfoxide, add into the reactor and stir, the temperature of the reactor is raised to 60°C, the stirring rate is 180rpm, after keeping warm and stirring for 15min, 30.0g of modified polyurethane is added into the reactor, after keeping warm and reacting for 60min, the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain a chain extended polyurethane.
[0100] S3. Preparation of hybrid polyurethane
[0101] Weigh: 10.0 g of allyltrimethoxysilane and 36.0 mL of dichloromethane are added to a low-temperature reactor and stirred. After the low-temperature reaction temperature is reduced to -80°C, ozone is introduced into the reactor at a rate of 0.5 L / min, and the reaction is kept warm for 15 minutes. After the reaction is completed, the reaction solution is collected after the temperature of the reactor is raised to room temperature to obtain an oxidized solution;
[0102] Weigh: 24.0 mL of oxidation solution and 8.0 g of dimethyl sulfide are added to the reactor, stirred at room temperature for 30 min at a stirring rate of 120 rpm. After the reaction is completed, the reaction solution is added to a rotary evaporator with a water bath temperature of 100° C. and distilled under reduced pressure until no liquid is produced to obtain modified silane;
[0103] Weigh: 36.0g of extended chain polyurethane, 8.0g of modified silane, 10.0g of 3-trifluoromethylpropiophenone, 1.6g of γ-alumina and 150.0mL of dimethyl sulfoxide and add them into a reactor. The temperature of the reactor is raised to 80°C and the reaction is kept warm for 3 hours. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain a hybrid polyurethane.
[0104] S4. Preparation of termination tape
[0105] Weigh: 60.0g perfluoropolyamide, 12.0g silicone oil, 12.0g acetone, 6.0g hexamethylenetetramine, 8.0g dibutyl phthalate and 1.6g 2,6-di-tert-butyl-p-cresol, mix the materials evenly and put them into a twin-screw extruder to melt and extrude them into a mold. After the materials are cooled, place the materials in a stretching machine, set the temperature of the stretching machine to 120°C, control the longitudinal stretching ratio to 6:1, and the transverse stretching ratio to 12:1. After the stretching is completed, transfer the film to a cooling system, set the temperature of the cooling system to 40°C, cool and mold for 2h to obtain a stretched film, cut it with a CNC machine tool to obtain a strip base layer with a thickness of 30μm and a width of 20mm, and roll the base layer 200 with a winder;
[0106] Weigh: 80.0g hybrid polyurethane, 24.0g petroleum resin, 12.0g hexamethylenetetramine, 8.0g dibutyl phthalate, 12.0g acetone and 1.2g anti-2,6-di-tert-butyl-p-cresol. Mix the materials evenly and put them into a twin-screw extruder for melt extrusion coating on the upper surface of the base layer 200 to obtain a pressure-sensitive adhesive layer 100 with a thickness of 30μm. Put the coated base layer 200 into a drying oven at a temperature of 15°C for cold air drying. The cold air temperature is 15°C and the wind speed is 10m / s. Dry until the coating temperature drops to room temperature. After drying, use a winder to wind it up, and control the winding stress at 50N / m to obtain a termination tape.
[0107] Example 3
[0108] This embodiment is used to provide an electrolyte-resistant and high-temperature-resistant lithium battery termination tape and a preparation method thereof, comprising the following steps:
[0109] S1. Preparation of perfluoropolyamide
[0110] Weigh: 16.0 g of 5,5'-methylenedisalicylic acid, 10.0 g of 2,4-diamino-6-[4-(trifluoromethyl)phenyl]-1,3,5-triazine, 0.8 g of triethylamine and 100.0 mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 80°C, keep the temperature for 4 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain a modified polyamide;
[0111] Weigh: 24.0 g of modified polyamide, 8.0 g of perfluorooctane sulfonyl fluoride, 0.8 g of triethylamine and 120.0 mL of dimethyl sulfoxide, add into a reactor and stir, lower the temperature of the reactor to 3°C, keep warm and stir for 2 hours, after the reactor is cooled to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain perfluoropolyamide.
[0112] S2. Preparation of chain-extended polyurethane
[0113] Weigh: 12.0 g of 2,3,5,6-tetrafluorophenylenedimethanol, 1.5 g of triethylamine and 150.0 mL of dimethyl sulfoxide are added to a reactor and stirred. The temperature of the reactor is raised to 55° C., the stirring rate is 150 rpm, and after heat preservation and stirring for 12 minutes, 20.0 g of 1,3-diisocyanatotoluene is added to the reactor. After heat preservation and reaction for 50 minutes, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90° C., and reduced pressure distillation is performed until no liquid is produced to obtain a modified polyurethane;
[0114] Weigh: 9.0 mL of 20-30 wt% hydrogen peroxide aqueous solution and 1.0 g of triethylamine are added to a reaction kettle, stirred at room temperature for 3 min at a stirring rate of 50 rpm to obtain an epoxidation solution;
[0115] Weigh: 12.0g of 1,3,5-triacyl cyanurate, 48.0mL of dichloromethane and 3.0g of tetrabutylammonium bromide are added to a reactor and stirred. After the temperature of the reactor is raised to 40°C, 40.0mL of epoxidation liquid is added to the reactor and the reaction is kept warm for 2h. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain an epoxidation chain extender;
[0116] Weigh: 18.0 g of epoxidation chain extender, 6.0 g of diethyl phosphite, 1.0 g of triethylamine and 100.0 mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 70°C, keep the temperature for 2 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain a modified chain extender;
[0117] Weigh: 8.0g of modified chain extender, 1.2g of triethylamine and 150.0mL of dimethyl sulfoxide, add into the reactor and stir, the temperature of the reactor is raised to 55°C, the stirring rate is 150rpm, after keeping warm and stirring for 12min, 32.0g of modified polyurethane is added into the reactor, after keeping warm and reacting for 50min, the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain a chain extended polyurethane.
[0118] S3. Preparation of hybrid polyurethane
[0119] Weigh: 10.0 g of allyltrimethoxysilane and 32.0 mL of dichloromethane are added to a low-temperature reactor and stirred. After the low-temperature reaction temperature is reduced to -80°C, ozone is introduced into the reactor at a rate of 0.4 L / min, and the reaction is kept warm for 12 minutes. After the reaction is completed, the reaction solution is collected after the temperature of the reactor is raised to room temperature to obtain an oxidized solution;
[0120] Weigh: 24.0 mL of oxidation solution and 8.0 g of dimethyl sulfide are added to the reactor, stirred at room temperature for 24 min, and the stirring rate is 100 rpm. After the reaction is completed, the reaction solution is added to a rotary evaporator with a water bath temperature of 90° C., and distilled under reduced pressure until no liquid is produced to obtain modified silane;
[0121] Weigh: 36.0g of extended chain polyurethane, 8.0g of modified silane, 10.0g of 3-trifluoromethylpropiophenone, 1.2g of γ-alumina and 150.0mL of dimethyl sulfoxide and add them into a reactor. The temperature of the reactor is raised to 70°C and the reaction is kept warm for 3 hours. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain a hybrid polyurethane.
[0122] S4. Preparation of termination tape
[0123] Weigh: 55.0g perfluoropolyamide, 10.0g silicone oil, 12.0g acetone, 6.4g hexamethylenetetramine, 8.4g dibutyl phthalate and 1.8g 2,6-di-tert-butyl-p-cresol, mix the materials evenly and put them into a twin-screw extruder to melt and extrude them into a mold. After the materials are cooled, place the materials in a stretching machine, set the temperature of the stretching machine to 110°C, control the longitudinal stretching ratio to 5:1, and the transverse stretching ratio to 10:1. After the stretching is completed, transfer the film to a cooling system, set the temperature of the cooling system to 30°C, cool and mold for 2h to obtain a stretched film, cut it with a CNC machine tool to obtain a strip base layer with a thickness of 25μm and a width of 15mm, and roll the base layer 200 with a winder;
[0124] Weigh: 72.0g hybrid polyurethane, 16.0g petroleum resin, 12.0g hexamethylenetetramine, 8.0g dibutyl phthalate, 12.0g acetone and 1.6g 2,6-di-tert-butyl-p-cresol, mix the materials evenly, put them into a twin-screw extruder for melt extrusion coating on the upper surface of the base layer 200, and obtain a pressure-sensitive adhesive layer 100 with a thickness of 25μm. Put the coated base layer 200 into a drying oven at a temperature of 12°C for cold air drying. The cold air temperature is 12°C and the wind speed is 9m / s. Dry until the coating temperature drops to room temperature. After drying, use a winder to wind it up, and control the winding stress at 40N / m to obtain a termination tape.
[0125] Comparative Example 1
[0126] The difference between this comparative example and Example 3 is that the step of fluorinating the modified polyamide in step S1 is eliminated, and in step S3, an equal amount of the modified polyamide is used to replace the perfluoropolyamide.
[0127] Comparative Example 2
[0128] The difference between this comparative example and Example 3 is that step S3 is eliminated and an equal amount of chain-extended polyurethane is used to replace the hybrid polyurethane.
[0129] Comparative Example 3
[0130] The difference between this comparative example and Example 3 is that part of the steps in step S2 and step S3 are eliminated, and an equal amount of modified polyurethane is used to replace the hybrid polyurethane.
[0131] Performance Test:
[0132] The tape tensile strength, elongation at break, 180° peel strength of the adhesive layer, annular initial adhesion, temperature resistance and electrolyte resistance of the termination tapes prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard T / UNP 4-2022 "Technical Specifications for Expandable Tapes for Lithium Batteries";
[0133] The limiting oxygen index of the termination tapes prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 26526-2011 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test";
[0134] The volume wear of the base layer of the termination tapes prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)". The specific test results are shown in Table 1.
[0135] Table 1-Performance test data of each sample
[0136]
[0137]
[0138] Data Analysis:
[0139] Comparative analysis of the data in Table 1 above shows that the termination tape prepared by the present invention has a length and width change rate of 2% after high-temperature baking at 85°C for 2 hours, and the tape does not change color after being immersed in an electrolyte at 85°C for 2 hours. The electrolyte is stable, the limiting oxygen index is as high as 38.8%, and the volume wear is only 10 mm 3 At the same time, the tensile strength, elongation at break and 180° peel strength of the adhesive layer in the longitudinal direction are 45%, 12% and 0.5N·25mm respectively. -1 In the width direction, the tensile strength, elongation at break and 180° peel strength of the adhesive layer are 85%, 28% and 0.6N·25mm respectively. -1 , all data are better than the comparative example, indicating that:
[0140] In the process of preparing the lithium battery termination tape, the present invention prepares a perfluoropolyamide as the main component of the base layer. In the process of preparing the perfluoropolyamide, a triazine ring having a benzene ring and a fluorine group and an organic matter having a large number of benzene rings are first selected as monomers, and a modified polyurethane with high mechanical strength, electrolyte resistance and high temperature resistance is synthesized through polymerization reaction. A large number of fluorine groups are introduced into the organic chain segment after polymerization with perfluorooctane sulfonyl fluoride, so that the electrolyte resistance and high temperature resistance of the material are further improved, and finally the perfluoropolyamide is obtained, and a large number of hydroxyl groups exist on the surface of the perfluoropolyamide. In the process of high-temperature coating of the pressure-sensitive adhesive layer, the residual hydroxyl groups on the surface are further combined with the isocyanate groups in the hybrid polyurethane component in the pressure-sensitive adhesive to form a stable structure linked by chemical bonds, so that the structure of the termination tape is further stabilized, and the mechanical strength and wear resistance of the termination tape are improved;
[0141] In the process of preparing a lithium battery termination tape, the present invention prepares a hybrid polyurethane as the main component of a pressure-sensitive adhesive layer. In the process of preparing the hybrid polyurethane, firstly, a monomer with a large number of fluorine groups is selected to prepare a modified polyurethane so that it has certain chemical stability and high temperature resistance, and triazine ring organic matter is modified to obtain a modified chain extender through epoxidation and ring-opening reaction. The modified chain extender is cross-linked to make the modified polyurethane produce a complex spatial network structure to obtain an extended chain polyurethane, so that the mechanical properties of the material are further improved, and the active functional groups on the silane coupling agent are further oxidized to obtain modified silane. The modified silane and the organic matter with a large number of fluorine groups are used to modify the extended chain polyamide. Through the introduction of the silane coupling agent and the fluorine group, the bonding force between the material and the inorganic surface, the high temperature resistance and the electrolyte resistance are further improved, and finally the hybrid polyurethane is prepared.
[0142] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0143] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0144] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Electrolyte-resistant and high-temperature-resistant lithium battery termination tape, characterized in that: It comprises a pressure-sensitive adhesive layer (100) and a base layer (200); The pressure-sensitive adhesive layer (100) comprises the following raw materials by weight: 60-80 parts of hybrid polyurethane, 10-30 parts of tackifier, 10-15 parts of thermosetting agent, 5-10 parts of plasticizer, 10-15 parts of solvent and 0.5-2 parts of antioxidant; The base layer (200) comprises the following raw material composition by weight: 50-60 parts of perfluoropolyamide, 10-15 parts of anti-adhesive agent, 10-20 parts of solvent, 5-8 parts of thermal curing agent, 5-10 parts of plasticizer and 0.5-2 parts of antioxidant.
2. The electrolyte-resistant and high-temperature-resistant lithium battery termination tape according to claim 1, characterized in that: The preparation method of the hybrid polyurethane comprises the following steps: A1. Add allyltrimethoxysilane and dichloromethane to a low-temperature reaction kettle and stir. After the low-temperature reaction temperature is reduced to -80°C, ozone is introduced into the reaction kettle at a rate of 0.2-0.5L / min. The reaction is kept warm for 10-15min. After the reaction is completed, the reaction solution is collected after the temperature of the reaction kettle is raised to room temperature to obtain an oxidizing solution. A2, adding the oxidizing liquid and dimethyl sulfide into the reactor, stirring at room temperature for 20-30 minutes, and post-treating to obtain modified silane; A3. Add chain-extended polyurethane, modified silane, 3-trifluoromethylpropiophenone, γ-alumina and dimethyl sulfoxide into a reactor, increase the temperature of the reactor to 60-80°C, keep the reaction temperature for 2-3 hours, and obtain hybrid polyurethane after post-treatment.
3. The electrolyte-resistant and high-temperature-resistant lithium battery termination tape according to claim 2, characterized in that: In step A1, the dosage ratio of allyltrimethoxysilane and dichloromethane is 3-5g:15-20mL; in step A2, the stirring rate is 80-120rpm, and the dosage ratio of the oxidizing solution and dimethyl sulfide is 10-15mL:3-5g; in step A3, the dosage ratio of the extended polyurethane, modified silane, 3-trifluoromethylpropiophenone, γ-alumina and dimethyl sulfoxide is 15-20g:2-5g:4-6g:0.5-0.8g:60-80mL.
4. The electrolyte-resistant and high-temperature-resistant lithium battery termination tape according to claim 2, characterized in that: The preparation method of the chain-extended polyurethane is: B1. Add 1,3,5-triacyl cyanurate, dichloromethane and tetrabutylammonium bromide into a reactor and stir. After the temperature of the reactor is raised to 30-50° C., add the epoxidation liquid into the reactor, keep the temperature for 1-2 hours, and perform post-treatment to obtain an epoxidation chain extender. B2, adding the epoxidation chain extender, diethyl phosphite, triethylamine and N,N-dimethylformamide into the reactor, raising the temperature of the reactor to 60-80°C, keeping the temperature for reaction for 1-3h, and post-treating to obtain the modified chain extender; B3. Add the modified chain extender, triethylamine and dimethyl sulfoxide into the reactor and stir. The temperature of the reactor is raised to 50-60°C. After stirring for 10-15 minutes, the modified polyurethane is added into the reactor. After the reaction is carried out for 40-60 minutes, the chain-extended polyurethane is obtained by post-treatment.
5. The electrolyte-resistant and high-temperature-resistant lithium battery termination tape according to claim 4, characterized in that: In step B1, the amount ratio of 1,3,5-triacyl cyanurate, dichloromethane and tetrabutylammonium bromide to the epoxidation liquid is 5-8g:20-30mL:1.2-1.6g:20-25mL, and the epoxidation liquid is prepared by configuring 20-30wt% aqueous hydrogen peroxide solution and triethylamine in an amount ratio of 8-10mL:1g; in step B2, the amount ratio of epoxidation chain extender, diethyl phosphite, triethylamine and N,N-dimethylformamide is 8-10g:2-3g:0.3-0.5g:50-60mL; in step B3, the stirring rate of the reactor is 120-180rpm, and the amount ratio of modified chain extender, triethylamine, dimethyl sulfoxide and modified polyurethane is 3-5g:0.5-0.8g:60-80mL:15-20g.
6. The electrolyte-resistant and high-temperature-resistant lithium battery termination tape according to claim 4, characterized in that: The preparation method of the modified polyurethane is as follows: 2,3,5,6-tetrafluorophenylenedimethanol, triethylamine and dimethyl sulfoxide are added into a reaction kettle and stirred, the temperature of the reaction kettle is increased to 50-60°C, and after being kept warm and stirred for 10-15 minutes, 1,3-diisocyanatotoluene is added into the reaction kettle, and after being kept warm and reacted for 40-60 minutes, the modified polyurethane is obtained by post-treatment.
7. The electrolyte-resistant and high-temperature-resistant lithium battery termination tape according to claim 4, characterized in that: The stirring rate of the reactor is 120-180 rpm, the dosage ratio of 2,3,5,6-tetrafluorophenylenedimethanol, triethylamine, dimethyl sulfoxide and 1,3-diisocyanatotoluene is 5-8 g: 0.5-0.8 g: 60-80 mL: 8-12 g, and the post-treatment comprises: after the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100° C., and the reduced pressure distillation is performed until no liquid is extracted to obtain a modified polyurethane.
8. The electrolyte-resistant and high-temperature-resistant lithium battery termination tape according to claim 1, characterized in that: The preparation method of the perfluoropolyamide comprises the following steps: C1, adding 5,5'-methylenedisalicylic acid, 2,4-diamino-6-[4-(trifluoromethyl)phenyl]-1,3,5-triazine, triethylamine and dimethyl sulfoxide into a reaction kettle, raising the temperature of the reaction kettle to 60-80°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain modified polyamide; C2. Add modified polyamide, perfluorooctane sulfonyl fluoride, triethylamine and dimethyl sulfoxide into a reactor and stir. Lower the temperature of the reactor to 0-5°C, keep warm and stir for 1-2 hours, and perform post-treatment to obtain perfluoropolyamide.
Citation Information
Patent Citations
Lithium ion battery termination adhesive tape with corrosion resistance
CN115340828A
Electrolyte-resistant and high-temperature-resistant lithium battery termination adhesive tape and preparation method thereof
CN117757373A
